Penelitian Pelayanan Sirkulasi di Perpustakaan Perguruan Tinggi dalam Database Google Scholar: Narrative Literature Review - Arini, Salsabila Putri; Anwar, Rully Khairul; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Circulation service is a service to the circulation of library materials owned by the library. Generally regarding member registration, borrowing, returns, extension of time, and making statistics. The purpose of writing this article is to find out the role of librarians and innovation in circulation services in college libraries. This study uses the method of literature study or narrative literature review from five references originating from the Google Scholar database, spanning 2013-2023. Based on the results of the analysis, there are several problems in circulation services in tertiary institutions. This problem is usually related to budgetary funds, human resources, lack of information and technology systems, user behavior, and management of the circulation service system. In this case, librarians have an important role to be responsible for managing, operating, and developing information systems and circulation services, as well as various obstacles and problems in libraries. Therefore, innovation and collaboration are needed in tertiary library circulation services with careful consideration from a cost-to-utilization perspective, as well as periodic evaluations to test the success and effectiveness of these innovations.Keywords: College Library, Circulation Services, Librarian